Intraoperative Hemodynamic Profile: Evaluation of Mean Arterial Pressure in Patients Undergoing General Anesthesia - Suyanti, Suyanti; Widyastuti, Yuli; Aisyah, Indah Nur (Genius Journal, 2026)
Introduction: Intraoperative hemodynamic fluctuations during general anesthesia are clinically important because reduced Mean Arterial Pressure (MAP) may compromise organ perfusion and contribute to postoperative complications. Despite growing awareness of the need for hemodynamic control, variations in MAP across different patient characteristics and surgical types remain insufficiently documented in clinical practice. Objective: This study aimed to evaluate intraoperative MAP patterns in patients undergoing general anesthesia and to identify variations based on demographic and clinical factors. Method: A descriptive observational design was applied to 61 elective surgical patients with ASA physical status I–II at RSI Sultan Agung Semarang. Intraoperative MAP measurements were recorded using standardized patient monitoring systems. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Result: The mean intraoperative MAP was 69.49 ± 4.32 mmHg. Although most respondents maintained normotensive values, 8.2% experienced hypotension below the 65 mmHg threshold. Higher MAP values were observed in patients aged 41–50 years, those with ASA II status, and those undergoing lower abdominal surgery. Lower MAP values were more common in urology procedures and among ASA I patients. Conclusion: Although the overall MAP level remained within the acceptable clinical range, the presence of intraoperative hypotension in a subset of patients underscores the importance of proactive, individualized hemodynamic monitoring. Variations in MAP across demographic and surgical factors highlight the need for patient-specific hemodynamic targets to ensure optimal intraoperative safety.